PENGARUH PENGGUNAAN CEROBONG DAN BLOWER PADA KONSTRUKSI WATER HEATER GAS LPG - Hari Kristianto (Nozel : Jurnal Pendididikan Teknik Mesin, 2021)
Hot / warm water is needed, especially for bathing purposes. Hot air used for bathing purposes is usually mixed with cold air whose mixture temperature reaches 35ºC to 40ºC. To take advantage of hot water, one of them is to use a water heater which is commonly called a water heater. The aims of this study were (1) to design and manufacture a water heater, (2) to obtain the relationship between air flow and the temperature of the air coming out of the water heater, (3) to obtain a relationship between air flow and the rate of heat transfer received and (4) to obtain a relationship between the flow rate of the water heater. water with water heater efficiency.The designed water heater produces variations in exhaust gas disposal and to obtain data, research is carried out in the laboratory.The results of the research process found that a water heater with a chimney and a blower is the best construction among the 2 other models in this study, with the data: (1) Water heater that is able to compete with water heaters on the market, which is able to produce air heat with a temperature of: 35.4 oC at a flow rate of 7.2 liters/minute, (2) The relationship between the flow of air (m) and the temperature of the water heater (To) can be expressed by the equation: To = –0.2215m3 + 4, 5633m2 – 29.935m + 96,878 (m in liters/minute, To in oC) (3) The relationship between flowing water and the rate of heat transfer is expressed by the equation: qair = –2.6026m3 + 6.9591m2 + 302.15m + 2536,7 (m in liters/minute, Qair in watts) (d) The relationship between flowing water and efficient water heaters can be expressed by the equation: = –0.0376m3 + 0.1006m2 + 4.3666m + 36.66 ( m in liters/minute, in percent).